2019
DOI: 10.1097/mao.0000000000002148
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-5 (PDE-5) Inhibitors and Ototoxicity: A Systematic Review

Abstract: Objective: This study explores the current literature regarding associations between phosphodiesterase-5 (PDE-5) inhibitors and ototoxicity and provides a detailed summary and discussion of the findings. Data Sources: A comprehensive electronic search of PubMed/MEDLINE, Scopus, and Cochrane Library for studies published from database inception through March 21, 2018. Study Selection: Basic science articles, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…One explanation has been that PDE-5 decreases cGMP degradation, which may promote activation of mean arterial pressure kinase-mediated cellular stress responses and apoptosis. 28 Although the mechanisms described previously are among those more commonly studied, other mechanisms of ototoxicity have yet to be investigated. It is also worth noting that certain ototoxic medications might even be otoprotective against other ototoxic medications.…”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation has been that PDE-5 decreases cGMP degradation, which may promote activation of mean arterial pressure kinase-mediated cellular stress responses and apoptosis. 28 Although the mechanisms described previously are among those more commonly studied, other mechanisms of ototoxicity have yet to be investigated. It is also worth noting that certain ototoxic medications might even be otoprotective against other ototoxic medications.…”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
“…Hearing loss attributed to phosphodiesterase‐5 (PDE‐5) inhibitors, such as sildenafil, is believed to involve the nitric oxide–cyclic guanosine monophosphate (cGMP) pathway of cochlear vascular endothelium. One explanation has been that PDE‐5 decreases cGMP degradation, which may promote activation of mean arterial pressure kinase‐mediated cellular stress responses and apoptosis 28 …”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
“…Most of the drugs and chemicals known to cause hearing loss and damage to the sensory hair cells, neurons and support cells in the cochlea, have been largely identified and extensively studied over the past 100 years (Campbell and Le Prell, 2018, Manna et al, 2019, Prakash Krishnan Muthaiah et al, 2017, Roth and Salvi, 2016, Rybak, 1986. Nevertheless, considerable research continues to be conducted on these ototoxic compounds to elucidate the mechanisms by which they induce their toxic effects and to develop new methods to mitigate their ototoxic effects (Benkafadar et al, 2017, Kim et al, 2011, Kim et al, 2008, Majumder et al, 2015, Youn et al, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly reported PTs were hypoacusis and tinnitus, other highly reported PTs involved deafness, deafness unilateral, which was consistent with the published literature. Manna et al summarized the clinical symptoms of case reports involving PDE5Is-related hearing impairment, they found that 75% of the cases indicated unilateral deficits, while 22% reported tinnitus 22 . Drugs-related hearing impairment usually indicates poor prognosis, which is the same for PDE5Is.…”
Section: Discussionmentioning
confidence: 99%